1996
DOI: 10.1210/mend.10.10.9121485
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear receptor coactivators and corepressors.

Abstract: The nuclear receptors belong to a superfamily of proteins, many of which are ligand-regulated, that bind to specific DNA sequences and control specific gene transcription. Recent data show that, in addition to contacting the basal transcription machinery directly, nuclear receptors inhibit or enhance transcription by recruiting an array of coactivator or corepressor proteins to the transcription complex. In this review we define the properties of these putative coregulatory factors; we describe the basal and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
414
0
5

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 460 publications
(423 citation statements)
references
References 49 publications
4
414
0
5
Order By: Relevance
“…They influence the magnitude of transcriptional activation or repression and alter the dose-responsive profiles to the ligands depending on the natures of the ligand (6). The involvement of coregulators, coactivators such as SRC-1, GRIP-1, and corepressors, such as SMRT (silencing mediator for retinoid and thyroid hormone receptor), nuclear receptor corepressor-1, in transcriptional regulation by the ER is now well established (32,33). Therefore, we tested the possibility that CAR interferes with the ER transactivation by squelching the ER coactivators, GRIP-1 and SRC-1.…”
Section: Discussionmentioning
confidence: 99%
“…They influence the magnitude of transcriptional activation or repression and alter the dose-responsive profiles to the ligands depending on the natures of the ligand (6). The involvement of coregulators, coactivators such as SRC-1, GRIP-1, and corepressors, such as SMRT (silencing mediator for retinoid and thyroid hormone receptor), nuclear receptor corepressor-1, in transcriptional regulation by the ER is now well established (32,33). Therefore, we tested the possibility that CAR interferes with the ER transactivation by squelching the ER coactivators, GRIP-1 and SRC-1.…”
Section: Discussionmentioning
confidence: 99%
“…Corepressors physically bind to T3Rs and RARs in the absence of hormone, a context in which these receptors typically repress. Addition of hormone leads to release of the corepressor, the association of coactivators, and conversion of the receptor to a positive enhancer of transcription (26)(27)(28)(29)(30)(31)(32)(33)(34). Given the central role of corepressors in the actions of the normal RARs, we examined the role of these cofactors in the actions of the PML-RAR␣ and PLZF-RAR␣ oncoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of hormone converts these receptors into transcriptional activators, a process that correlates with dissociation of the corepressors from the receptor and a corresponding recruitment of a novel set of coactivator proteins (26)(27)(28)(29)(30)(31)(32)(33)(34). In vertebrates, corepressors are encoded by two known, interrelated loci, denoted SMRT (or TRAC) and N-CoR (or RIP13), with each locus expressed as a variety of alternatively spliced mRNAs (e.g., TRAC-1, TRAC-2, RIP13A; refs.…”
mentioning
confidence: 99%
“…For example, gene activation by nuclear hormone receptors (NHRs) has recently been shown to include additional proteins that associate directly with receptors, including the estrogen receptor (see : Horwitz et al, 1996;Katzenellenbogen et al, 1996). Biochemical and interactive cloning methods have led to isolation of 120 (Le Douarin et al, 1995), 125 (Onate et al, 1995), 140 (Cavailles et al, 1994(Cavailles et al, , 1995Halachmi et al, 1994), 160 (Halachmi et al, 1994;Cavailles et al, 1994), 168 (Chen and Evans, 1995) and 270 (Horlein et al, 1995) kDa proteins shown to associate with ligand-bound NHRs and function as positive (co-activators) or negative (corepressors) of nuclear receptor action by modulating interaction with the basal transcription complex.…”
Section: Introductionmentioning
confidence: 99%